Comparing the health of refugee and asylee patients with that of non-refugee immigrant and US-born patients in a large Urban clinic - Eva Raphael; Michelle Barton; Katrin Jaradeh; Cristy Dieterich; Rita Hamad (BMC, 2023)
Abstract Objectives To compare disease burden in refugee/asylee, non-refugee immigrant, and US-born patients in the largest safety net clinic in San Francisco, California. Methods This is a retrospective chart review including 343 refugee/asylee, 450 immigrant, and 202 US-born patients in a San Francisco clinic from January 2014 to December 2017. Using electronic medical records, we compared prevalence of several diseases by immigration status. Using Poisson regression models with robust variance, we assessed association of diseases with immigration status, adjusting for sociodemographic characteristics. Results Diagnoses of non-communicable chronic diseases were less common in refugees/asylees, who had a greater risk of being diagnosed with mental health conditions. In Poisson regression models adjusted for sociodemographic characteristics, compared with refugees/asylees, US-born patients were more likely to have hypertension (IRR[CI] = 1.8 [1.0, 3.7]) and less likely to have depression (IRR[CI] = 0.5 [0.3, 0.8]). US-born (IRR[CI] = 0.06 [0.01, 0.2]) and immigrant patients (IRR[CI] = 0.1 [0.06, 0.2]) were less likely to have post-traumatic stress disorder. Conclusions We uncover differences in burden of non-communicable chronic diseases and mental health by immigration status. These results highlight the importance of clinical screenings and research on disease burden in refugees.